1994
DOI: 10.1007/bf00197387
|View full text |Cite
|
Sign up to set email alerts
|

Serous oligocystic and ill-demarcated adenoma of the pancreas: a variant of serous cystic adenoma

Abstract: Serous cystic tumours of the pancreas are uncommon and are usually classified as microcystic adenomas (MCA). As new types of serous cystic tumours of this organ have been reported we reviewed a series of 14 lesions and from macroscopic findings two groups were distinguished: ten tumours revealed the features of MCA, while four were clearly distinct from MCA. Grossly, the latter tumours showed only few cysts which were irregularly assembled in fibrous stroma. On the cut surface, there was neither a central stel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 17 publications
2
52
0
1
Order By: Relevance
“…The review of series of five and more serous cystic neoplasms [7, 10, 21, 25, 26, 27, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49]showed that serous cystadenoma of the pancreas presents at an earlier age (mean 61 years) than serous cystadenocarcinoma (mean 66 years; table 2 [5, 6, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28]). This difference was almost statistically significant (p = 0.056).…”
Section: Resultsmentioning
confidence: 99%
“…The review of series of five and more serous cystic neoplasms [7, 10, 21, 25, 26, 27, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49]showed that serous cystadenoma of the pancreas presents at an earlier age (mean 61 years) than serous cystadenocarcinoma (mean 66 years; table 2 [5, 6, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28]). This difference was almost statistically significant (p = 0.056).…”
Section: Resultsmentioning
confidence: 99%
“…149,150 Oligocystic (macrocystic) variant of serous cystadenoma Although the vast majority of serous cystadenomas exhibit a microcystic growth pattern, rare examples are oligocystic (megacystic, macrocystic), that is, composed of fewer but larger loculi. [133][134][135]137,151 The epithelial lining of these cysts may become denuded, and it may be difficult to distinguish oligocystic serous cystadenomas from mucinous neoplasms or pseudocysts. 152 unless the lesion is extensively sampled and examined carefully to identify the characteristic glycogen-rich clear cells.…”
Section: Serous Cystadenomamentioning
confidence: 99%
“…The size of the lesions was measured from the pathological specimen, when available, or from radiological imaging. Serous cystic tumors were classified as ‘microcystic’ if composed of multiple (number >6) and small (diameter <20 mm) cysts [18], as ‘oligocystic’ when composed largely or exclusively of macrocysts (diameter ≥20 mm) that were few in number or containing only a single macrocyst of any size with a few satellite cysts observed on microscopic examination [10, 16, 19] or as ‘solid’ when cystic lesions were not shown either in radiological imaging techniques or in the gross appearance of the specimen. Only microscopic examination is able to allow diagnosis [11, 12].…”
Section: Methodsmentioning
confidence: 99%
“…The correct identification of benign asymptomatic serous cystic tumors, and therefore the only possible indication for nonsurgical management of cystic neoplasms of the pancreas, is crucial. If the tumor type cannot be assessed with absolute certainty in the diagnostic workup, laparotomy is frequently necessary, even for incidentally found serous cystic tumors, for no other reason than for a definitive and complete histological diagnosis [14,15,16,17]. The purpose of the present study was to analyze our experience of consecutive cases of serous cystic tumors observed in our Pancreas Unit by means of general characteristics, clinical picture, diagnosis, management and outcomes.…”
Section: Introductionmentioning
confidence: 99%